Distrust, Relationality and Equity: A Response to Lacourt Suárez’s Trust, Learning and Social Growth Continuum - Martell, Gordon A. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2026)
My encounter with Lacourt Suárez’s (2026) Positive Leadership and its Impact on Improving the Climate in Chilean Schools. A Comparison between Teachers and School Leaders (Lacourt Suárez, 2026), compelled me to raise considerations for the role of trust in leadership and implications for effective teaching, successful students, and the achievement of social democratic goals. I wondered about how this equation manifests in contexts characterized by power differentials and intergenerational distrust. By reframing from a linear cause-and-effect to a cycle of negotiating trust and its implications for effectiveness, learning, and equity, we can not only recognize and encounter distrust but also embrace it in dissonance. Considering distrust as an attribute of calibrating relationships informed by social conditions that lie beneath the veneer of the certainty of trust, school leaders can discover the liberating discourse that results from interrogating trust and embracing the complexity and conditions that instigate distrust. Accepting these conditions as norms in building relationships based on authenticity has the potential to disrupt lingering power relationships in schools and society.